Adaptable Meta-Signal Tracking for Next-Generation Satellite Navigation Systems and LEO PNT - Nardin, Andrea; Dovis, Fabio; Zanier, Francesca; Melman, Floor (IEEE access, 2025)
In this study, the concept of multichannel signal tracking, previously discussed in the Global Navigation Satellite System literature, is expanded towards next-generation satellite navigation paradigms by leveraging multiple narrowband signals that are synchronously transmitted from the same satellite. This approach achieves a performance comparable to that of signals transmitted over larger bandwidths while effectively reallocating frequency resources to enhance the capacity of a wideband communication channel. This methodology can be applied to orthogonal signals, independently from their respective modulations and regardless of whether they are transmitted over different carrier frequencies or occupy the same bandwidth. The resulting architecture is tested in modern positioning, navigation and timing (PNT) scenarios, addressing in particular, the forthcoming low earth orbit (LEO) PNT paradigm to broad the technique's applicability also towards potential piggybacked services hosted by broadband megaconstellations (e.g. Kuiper, Starlink). The applicability domain of the signal tracking architecture is explored through a parametric analysis, assessing the performance under different combined conditions such as transmission bands, multichannel combination modes, Doppler profiles, and propagation conditions. This technique has shown large performance improvements with respect to conventional single channel processing, yielding code estimation error reductions above 90% in almost all the tested conditions.